Association between vaginal washing and detection of Lactobacillus by culture and quantitative PCR in HIV-seronegative Kenyan women: a cross-sectional analysis. (29th January 2019) - Lokken, Erica M; Manguro, Griffins Odhiambo; Abdallah, Amina; Ngacha, Caroline; Shafi, Juma; Kiarie, James; Jaoko, Walter; Srinivasan, Sujatha; Fiedler, Tina L; Munch, Matthew M; Fredricks, David N; McClelland, R Scott; et al.
Abstract : Objectives: Vaginal washing has been associated with reductions in cultivable Lactobacillus and an increased risk of both bacterial vaginosis (BV) and HIV infection. The effect of vaginal washing on the quantity of individual Lactobacillus species is not well characterised. This analysis tested the hypothesis that vaginal washing would be associated with a lower likelihood of Lactobacillus spp. detected by both culture and quantitative PCR (qPCR). Methods: We conducted a cross-sectional study of 272 HIV-seronegative women enrolled in an open-cohort study in Mombasa, Kenya. Vaginal washing and sexual risk behaviours were assessed using face-to-face interviews. Vaginal Lactobacillus spp. were detected using cultivation and PCR methods, with L. crispatus, L. jensenii and L. iners concentrations measured using qPCR assays targeting the 16S rRNA gene. Poisson regression with robust SEs was used to assess associations between vaginal washing and Lactobacillus detection by culture and qPCR. Results: Eighty percent (n=217) of participants reported vaginal washing in the prior week. One-fifth (n=58) of participants had BV by Nugent score. In unadjusted analysis, vaginal washing was associated with a 45% decreased likelihood of Lactobacillus spp. detection by culture (prevalence ratio (PR): 0.55, 95% CI 0.37 to 0.82). Adjusting for age and condomless sex in the prior week did not change the magnitude of the association (adjusted PR (aPR): 0.56, 95% CI (0.37 to 0.85). Vaginal washing was associated with approximately a 40% reduction in L. crispatus detection (aPR: 0.57, 95% CI 0.36 to 0.92), but was not significantly associated with L. jensenii (aPR: 0.68, 95% CI 0.42 to 1.09) or L. iners detection (aPR: 1.03, 95% CI 0.92 to 1.15). Conclusions: Vaginal washing in the prior week was associated with a significantly reduced likelihood of detecting cultivable Lactobacillus and L. crispatus by qPCR. Given associations between Lactobacillus detection and improved reproductive health outcomes, these results provide motivation for additional study of vaginal washing cessation interventions to improve vaginal health.